THE GAMKONORA DOCUMENTARY FILM: AN EXPERIENCE OF LANGUAGE REVITALISATION IN NORTH HALMAHERA - Imelda (TALENTA, 2021)
The documentary film is considered as a proper audio-visual medium for documenting traditions, but it has both advantages and challenges. Both issues explained in the paper based on the experience of making a cultural event documentary film of the Gamkonora people (https://www.youtube.com/watch?v=tCewhQOaNOk). This annual tradition held on the first day of every Eid al-Fitr by the Gamkonorans who live with other ethnic groups in West Halmahera Municipal, North Moluccas Province. This film is relatively effective in raising Gamkonoran identity awareness among the people, compared to language documentation in the form of a printed book or digital which requires a long process that spends much more energy. It is implied through comments on movies in social media and several films which produced spontaneously by young Gamkonorans through Youtube channels. In addition, discussions about the existence of the Gamkonora people are also present on social media such as Facebook, both in Ternate-Malay and Gamkonora languages. Besides the claims of documentary film effectiveness, it requires considerable preparation. Firstly, Gamkonora research team has done two years field researches and has done long discussion with movie crews before and after footages taking process. A researcher who took the role as a leader should have a storyline which is understandable by the film crews to guide them during footage takes. Another thing that should be done before is maintaining intensive communication with the four villages leaders of Gamkonoran (Gamkonora, Talaga, Tahafo, and Gamsungi villages), tua-tua adat, and key informants. Overall, among those complex processes, the most crucial aspect is deciding Dodengo as the tradition which touches every single Gamkonoran heart since it not only expressing their annual tradition, but also identity. It hoped that they realize how crucial their identity and they should do something to continue their existence. Thus, the documentary tradition of an ethnic group is a powerful medium to convey the message of their existence among the society that contains challenges, from the process before, during shooting, to the editing process to get the final result.